Composite H, W, Z Bosons: A Model Explaining the Different Experimental Values of their Masses Other Results: Pi-Meson, Nucleons, Heavy bosons, Dark Matter Masses - Fèvre, Raymond (European Journal of Applied Sciences, 2024)
The present article is the second version of an article published on June 2022 by “European Journal of Applied Sciences”. It develops a model initially published in ref. [1] and completed in ref. [2]. This is a quasi-classical quantum model of composite particles with ultra-relativistic (UR) constituents (leptons and quarks). The model is used to calculate the mass energy of three composite bosons: an UR tauonium, an UR bottomonium and an UR leptoquarkonium. The result is that these three hypothetic particles have masses close to 125 GeV: the Higgs boson mass energy. These results are recalled in the present article. Then the model is extended to calculate the mass energy of the W and Z bosons assumed to be composite particles, as well as those of the proton, the neutron, the pi-mesons and the composite bosons with a top quark constituent. For the W boson, the model gives two values: one has a mass equal to that measured recently at Fermilab (80.433 GeV), higher than the values measured so far. The other model value is according to the other measurements of the W boson mass. Finally, the model provides a hypothesis on dark matter.